Principles of Christian theology - Macquarrie, John (London SCM Press, 1977)
First published in 1966, Principles of Christian Theology is recognized as a classic in its presentation of the major themes of Christian thought in contemporary terms. This edition now includes new or additional material on topics such as the individual
Keywords: Christian theology. Theology, Doctrinal. Théologie dogmatique. Theologie Doctrinal theology